Undertaking loss reduction measures to prevent slope failures - Mariappan, Saravanan; Ali, Faisal; Mohamad, Ashaari; Abdullah, Che Hassandi Abdullah; Hassan, N.R.N.; Chong, S.; Huat, Low Tian (Academic Journals, 2010)
Landslides or slope failure has slowly become a major concern in Malaysia due to the rapid development of rural areas. Despite advances in science and technology, these events continue to result in human suffering, millions in property losses and environment degradation. It is a fact that with continuous population increase the economic development becomes more complex, while the economic and societal costs of landslides will continue to rise. Hence there is a need for a comprehensive program to reduce landslide losses that will marshal the capability of all levels of government and private sector. Successful and cost effective landslide loss reduction measures can and should be taken in the many jurisdictions facing landslide problems. Federal and state governments can prevent and reduce landslide losses through, creation of early warning and monitoring system, better policy and effective implementation, outlining design procedures, creation of local hazard mapping, land use management, building, grading controls, among others. Hence this paper addresses some of the measures proposed as part of loss reduction measures in order to minimize potential landslides or slope failures.